Increased Serum and Urinary Oxytocin Concentrations after Nasal Administration in Beagle Dogs - Temesi, Andrea; Thuróczy, Julianna; Balogh, Lajos; Miklósi, Ádám (Frontiers in Veterinary Science, 2017)
In recent years more and more studies have revealed the effect of extraneous oxytocin on the social behavior of dogs. The distribution of administered oxytocin in different physiologically relevant compartments is important because this knowledge forms the basis for the timing of behavior tests after the administration. Most behavioral studies rely on the non-invasive intranasal application of oxytocin. The aim of this study was to determine the time course of intranasal administered oxytocin secretion into blood and urine and also establish a connection between intranasal received oxytocin and urinary cortisol in dogs. In our experiment four dogs received 3 puffs, 12 IU intranasal oxytocin treatment, two dogs received 3 puffs intranasal placebo treatment. Blood and urine samples were collected immediately prior to the administration then regularly during 4 hours. After nasal oxytocin application, the serum oxytocin concentration increased, reached a maximum 15 minutes after the treatment and then rapidly returned to baseline levels 45 minutes later. The peak urinary oxytocin concentration occurred between 45 and 60 minutes after administration and returned to baseline levels slowly. We found considerable differences among individuals in the secretion of oxytocin in both the serum and the urinary oxytocin concentration measurements. Our results confirm that intranasally administered oxytocin passes into the blood stream. The time course of intranasally administered oxytocin secretion is similar to the time course of intravenously administered oxytocin secretion and the peak values are also similar in both the serum and the urinary oxytocin concentration measurements, although there are large individual differences.